Cognitive Impairment in Patients With Neuropsychiatric and Non-neuropsychiatric Systemic Lupus Erythematosus: A Systematic Review and Meta-analysis. (19th March 2018) - Zabala, Arantzazu; Salgueiro, Monika; Sáez-Atxukarro, Oihane; Ballesteros, Javier; Ruiz-Irastorza, Guillermo; Segarra, Rafael
Abstract: Objectives: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. Its most prevalent manifestation is neuropsychiatric SLE (NP-SLE), which is characterized by increased involvement of the nervous system, with relevant symptoms, such as marked cognitive deficits, which are directly involved in subsequent functional disability. The objective of this study is to identify and compare the profile of cognitive deficits in patients with NP-SLE and patients with non-neuropsychiatric SLE (nonNP-SLE) by means of a systematic review and meta-analysis.Methods: We performed a systematic literature search based on the key words "cogn* OR neurocogn* AND lupus AND neuropsychiatry*" and included articles published between April 1999 and December 2016. A total of 244 articles were retrieved. We excluded reviews and meta-analyses, experiments not performed in humans, and single case reports. We included studies that used standardized cognitive measures and had included at least the subgroups NP-SLE and non NP-SLE.Results: The meta-analysis was finally based on six studies, and 10 neuropsychological variables were examined. Significant differences were observed between the groups for six variables. In the remaining four variables, we observed marked heterogeneity between the groups or a low number of studies.Conclusions: The data obtained indicate greater cognitive impairment among NP-SLE patients than among nonNP-SLE patients, at least for the cognitive domains of visuomotor coordination, attention, executive function, visual learning and memory, and phonetic fluency. The identification and definition of cognitive deficits in SLE patients is necessary to develop adequate cognitive remediation programs to improve functional outcomes. ( JINS, 2018, 24, 629–639)